USE OF UBIQUITOUS COMPUTING FOR RETAIL INDUSTRY - PROF. KHURESHI M. A.; SWAPNIL MALI; SANGMESHWAR DARPHALE; TUSHAR MAHINDRAKAR (International Journal of Innovations in Engineering Research and Technology, 2021)
In today’s era of digitalization in every field and increasing digitalized systems being implemented in almost all the fields, this project centralizes on developing a system that tries to minimize the human resources, time and efforts in the payment system. Thecoreconceptofthisprojectistodevelopanapplicationforthemallsanditscustomersthatwill provide an effective shopping hence reducing the efforts from the customers as well as the vendors. The main objective of the project is to develop a system for the shopping malls and its customers which will provide ease of buying and selling of products. Also it minimizes the waiting time of the customers in the queue and saving time during the shopping using a guiding system and exploring a variety of products from the application.